2021
DOI: 10.1177/03080226211034420
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a power mobility device on occupational participation and quality of life for people with chronic diseases: A scoping review

Abstract: Introduction The aim was to explore occupational participation and quality of life (QoL) for power mobility device users with chronic disease. Methods Arksey and O’Malley’s framework for scoping reviews was used. Six data bases were searched using keywords: wheelchair, scooter, QoL and participation. Data were extracted with coding and thematic analysis performed. Results Forty-one articles met the inclusion criteria. An overarching theme of enhanced QoL was identified with subthemes of (i) independence, (ii) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
(198 reference statements)
0
2
0
Order By: Relevance
“…Indeed, Pritchard (2014) argued that spaces can become enabling for different body sizes through engagement with universal design and provision of equal access in the built environment. Physical environmental barriers are not exclusive to the obese population with Kemmis et al (2021) identifying how physical barriers can impact occupational participation for those in the chronic disease population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Pritchard (2014) argued that spaces can become enabling for different body sizes through engagement with universal design and provision of equal access in the built environment. Physical environmental barriers are not exclusive to the obese population with Kemmis et al (2021) identifying how physical barriers can impact occupational participation for those in the chronic disease population.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the chronic disease literature identified that there is a strong link between enhanced mobility through the use of a PMD and enhanced occupational participation (Kemmis et al, 2021). Sund and Brandt (2018) reported that satisfaction with a PMD and frequency of use is high for general users.…”
Section: Introductionmentioning
confidence: 99%